INCREASED CALCIUM AFFINITY OF A FUCOSYLATED CHONDROITIN SULFATE FROM SEA-CUCUMBER - Ruggiero, J.; Vieira, R. P.; Mourao, PAS (Elsevier B.V., 1994)
Calcium binding and charge distribution on a fucosylated chondroitin sulfate and a standard chondroitin 6-sulfate have been studied using a metallochromic indicator and conductimetric titrations. The fucosylated chondroitin sulfate has a similar to 5-fold greater affinity for calcium ions than the standard chondroitin 6-sulfate. Possibly, this increased affinity for calcium ions is due to the branches on the fucosylated chondroitin sulfate, since the calcium affinity of an unbranched, sulfated fucan is similar to that of the standard chondroitin 6-sulfate. More charged groups per disaccharide unit (and a shorter distance between these groups) also distinguish the fucosylated chondroitin sulfate from standard chondroitin 6-sulfate. Comparison between native and chemically modified (desulfated or carboxyl-reduced) polysaccharides suggests that the sulfate esters are responsible for the increased charge density of the fucosylated chondroitin sulfate and that the presence of the fucose branches does not alter the length of the repetitive units which compose the central core of chondroitin from sea cucumber. These results are consistent with the chemical studies of these two polysaccharides.